2021
DOI: 10.3389/fpsyt.2021.675839
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Use of Internet-Related Activities and Perceived Weight Stigma in Schoolchildren: A Longitudinal Study Across Different Epidemic Periods of COVID-19 in China

Abstract: Background: Social distancing and school suspension due to the coronavirus pandemic (COVID-19) may have a negative impact on children's behavior and well-being. Problematic smartphone use (PSU), problematic social media use (PSMU) and perceived weight stigma (PWS) are particularly important issues for children, yet we have a poor understanding of how these may have been affected by lockdowns and physical isolation resulting from COVID-19. This research aimed to understand how these psychosocial and behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 55 publications
(74 reference statements)
4
82
0
Order By: Relevance
“…South Korean fourth graders were more prone to smartphone addiction before COVID-19 than during [1]. However, problematic smartphone use prevalence was higher among Chinese primary schoolchildren during a COVID-19-related lockdown than before the pandemic [2]. Moreover, parents of American children aged 2-13 years reported that their children's problematic media use had increased during the pandemic as compared to in Spring 2019 [16].…”
Section: Smartphone Addiction Among Adolescents Since Covid-19mentioning
confidence: 90%
See 3 more Smart Citations
“…South Korean fourth graders were more prone to smartphone addiction before COVID-19 than during [1]. However, problematic smartphone use prevalence was higher among Chinese primary schoolchildren during a COVID-19-related lockdown than before the pandemic [2]. Moreover, parents of American children aged 2-13 years reported that their children's problematic media use had increased during the pandemic as compared to in Spring 2019 [16].…”
Section: Smartphone Addiction Among Adolescents Since Covid-19mentioning
confidence: 90%
“…Smartphone addiction is a common but growing issue among adolescents in South Korea [9], and studies in that country and others have shown that smartphone addiction and/or problematic smartphone use have increased among adolescents and adults since the COVID-19 pandemic [1,2,11,16,17]. South Korean fourth graders were more prone to smartphone addiction before COVID-19 than during [1].…”
Section: Smartphone Addiction Among Adolescents Since Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Motivated by the concerns about the mental health effects of increased ST among children, some findings have already been revealed under the current pandemic. For example, a longitudinal study conducted in China between January 2020 and June 2020 showed that school closures and lockdowns may have increased problematic smartphone use and depression [8]. A study that examined the association between Internet use and psychological distress at two time points, in early November 2019 before the COVID-19 outbreak and at the end of March 2020 during the COVID-19 outbreak, reported that schoolchildren who increased their Internet-related activity by 15 or 30 min daily under the pandemic had increased levels of psychological distress [9].…”
Section: Introductionmentioning
confidence: 99%